SOME APPROXIMATE PROPERTIES OF CESARO MEANS FOURIER SERIES - Bakuridze, Mzevinar; Bakuridze, Alexsander; Japaridze, Khatia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
The paper discusses the new property of the negative order Cesaro mean of the Fourier trigonometric series